2015
DOI: 10.1007/s00122-015-2624-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of common bunt resistance and plant height QTL in wheat

Abstract: Common bunt, also known as stinking smut, is caused by seed borne fungi Tilletia tritici (Bjerk.) Wint. [syn. Tilletia caries (DC.) Tul.] and Tilletia laevis Kühn [syn. Tilletia foetida (Wallr.) Liro.]. Common bunt is known to cause grain yield and quality losses in wheat due to bunt ball formation and infestation of the grain. The objectives of this research were to identify and map quantitative trait loci (QTL) for common bunt resistance, to study the epistatic interactions between the identified QTL, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 39 publications
5
61
3
Order By: Relevance
“…The two studies also used different inoculum sources: the Blizzard study used the common bunt races T-19 or T-19 and L-16, while this study used the composite dwarf bunt races. Additional common bunt HPR QTL have been reported from other resistance sources, including: 7A (Fofana et al 2008; Dumalasová et al 2012), 7B (Dumalasová et al 2012; Knox et al 2013), 5B (Dumalasová et al 2012; Singh et al 2016), 4D (Singh et al 2016), and 6D (Menzies, et al 2006; Singh et al 2016), while none of these HPR QTL were detected in the present study. Singh et al (2016) found that the common bunt HPR QTL co-localized with other beneficial traits including height and rust resistance.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The two studies also used different inoculum sources: the Blizzard study used the common bunt races T-19 or T-19 and L-16, while this study used the composite dwarf bunt races. Additional common bunt HPR QTL have been reported from other resistance sources, including: 7A (Fofana et al 2008; Dumalasová et al 2012), 7B (Dumalasová et al 2012; Knox et al 2013), 5B (Dumalasová et al 2012; Singh et al 2016), 4D (Singh et al 2016), and 6D (Menzies, et al 2006; Singh et al 2016), while none of these HPR QTL were detected in the present study. Singh et al (2016) found that the common bunt HPR QTL co-localized with other beneficial traits including height and rust resistance.…”
Section: Discussionmentioning
confidence: 92%
“…Additional common bunt HPR QTL have been reported from other resistance sources, including: 7A (Fofana et al 2008; Dumalasová et al 2012), 7B (Dumalasová et al 2012; Knox et al 2013), 5B (Dumalasová et al 2012; Singh et al 2016), 4D (Singh et al 2016), and 6D (Menzies, et al 2006; Singh et al 2016), while none of these HPR QTL were detected in the present study. Singh et al (2016) found that the common bunt HPR QTL co-localized with other beneficial traits including height and rust resistance. The three IDO444-derived QTL have no pleiotropic effect on other traits, such as coleoptile and root length (Li et al 2011), stripe rust (Chen et al 2012), grain yield, heading data, or height (Zhang et al 2014) previously mapped in this population.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous studies have shown that one resistance gene against Ug99 races of stem rust was identified in this region, as well as one resistance QTL to common bunt disease (caused by Tilletia tritici Wint and T . laevis Kühn), which was also co-located with a QTL for plant height [36,37]. It is unknown whether the gene for the Ug99 resistance and the QTL for common bunt resistance have any relationship with the plant canopy traits in this region.…”
Section: Discussionmentioning
confidence: 99%